2008
DOI: 10.1007/s10508-008-9394-1
|View full text |Cite
|
Sign up to set email alerts
|

Affect Regulation, Social Context, and Sexual Intercourse in Adolescents

Abstract: This study examined trajectories of positive and negative affect surrounding penile-vaginal sexual intercourse (sex) in adolescents and explored the influence of companionship on these trajectories. Using a handheld computer, sexually active adolescents (N = 67) reported momentary affect and sex events in response to several random signals each day for 1 week (1,777 reports, 266 sex events). Cubic spline regression analyses showed that positive affect began to increase before sex, peaked at the time sex was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 36 publications
4
33
1
Order By: Relevance
“…This yielded 35 articles for full-text review by both authors. Upon closer examination, we excluded 2 articles that used PDAs but did not transmit data using the internet17 18 and 10 articles that did not measure sexual risk behaviours as per our eligibility criteria 19–28. This left 23 articles representing 15 studies that used web-based diaries to examine sexual risk behaviour 2 3 29–49…”
Section: Resultsmentioning
confidence: 99%
“…This yielded 35 articles for full-text review by both authors. Upon closer examination, we excluded 2 articles that used PDAs but did not transmit data using the internet17 18 and 10 articles that did not measure sexual risk behaviours as per our eligibility criteria 19–28. This left 23 articles representing 15 studies that used web-based diaries to examine sexual risk behaviour 2 3 29–49…”
Section: Resultsmentioning
confidence: 99%
“…Individuals high in Self-Centered Impulsivity experience high levels of negative affect and subsequently may engage in RSB to reduce or escape negative emotions. Indeed, research has demonstrated that sex has the ability to regulate emotional states (e.g., Cooper, Agocha, & Sheldon, 2000;Shrier, Koren, Aneja, & de Moor, 2010). For example, in a sample of adolescents, Shrier and colleagues (2010) found that positive affect increased during sex and returned to baseline after sex.…”
Section: Rsb Psychopathic Personality Traits and Psychological Adjumentioning
confidence: 99%
“…However, it has been noted that despite the advantages of daily diary methods, when data are collected at the level of a given day, the within-day order of sexual activity and mood cannot be established; multiple time points within a day are needed to determine temporal relationships and this can sometimes be burdensome to participants (27). Using momentary sampling with handheld computers in a mixed-gender sample, Shrier and colleagues (28) were able to conduct such a study assessing multiple time points within each day and found that adolescents experienced increases in positive and decreases in negative affect before sex, and that there was no significant difference in affect trajectories by gender. While contributing important information to the field, this study focused on changes in affect around sexual activity, used a limited scale of “positive” emotions (happiness, well-being, and alertness), and did not relate findings to indicators of sexual safety.…”
Section: Introductionmentioning
confidence: 99%